Investigation of Water Quality and Fish Status of Karimganj Haor Area in Kishoreganj - Islam, MS; Jahan, J; Mou, MA; Kabir, MH; Uddin, MJ (Journal of Environmental Science and Natural Resources, 2018)
The study was conducted to investigate the physicochemical parameters and anionic constituents in water of the haor area of Karimganj during the period from October to December 2016. The water samples were collected from 3 different sampling stationsas St-1 (Bailabeel), St-2 (Ummabeel) and St-3 (Alkharabeel) for analyzing the temperature, electrical conductivity (EC), total dissolved solid (TDS), pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), alkalinity, hardness, fluoride (F-), chloride (Cl-), bromide (Br-), nitrite (NO2 -) , nitrate (NO3 -), and sulphate (SO4 2-) in water. The study also assessed the fish status of the Karimganjhaor area. The result of the study showed that the mean temperature (26.2 °C) of water was within the standard limit. The mean EC and TDS contents were 555 μS/cm and 526 mg/l, respectively which was satisfactory level for aquatic organisms. The mean DO (6.7 mg/l) content was favorable but BOD (2.7 mg/l) content indicated some extent of organic waste pollution. The mean pH and alkalinity were 7.30 and 338 mg/l, respectively indicated alkaline condition in haor water, and whereas hardness was 122 mg/l revealed that the water was suitable for fish production. The mean concentration of F-, Cl-, Br-, NO2 - , NO3 -, and SO4 2- were 0.35, 130.3, 0.16, 3.38, 34.84 and 85.60 mg/l, respectively depicted that the water were poorly improvised with these anionic constituents. J. Environ. Sci. & Natural Resources, 10(2): 19-27 2017